2020
DOI: 10.26496/bjz.2014.63
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue discrimination with contrast agents using micro-CT scanning

Abstract: The use of high resolution, three-dimensional visualization has been receiving growing interest within life sciences, with non-invasive imaging tools becoming more readily accessible. Although initially useful for visualizing mineralized tissues, recent developments are promising for studying soft tissues as well. Especially for micro-CT scanning, several X-ray contrast enhancers are performant in sufficiently contrasting soft tissue organ systems by a different attenuation strength of X-rays. Overall visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 61 publications
1
105
0
1
Order By: Relevance
“…During this time, the specimen and solution were set to mix on an orbital shaker, kept at room temperature, and covered with foil to prevent photoreaction. PMA is a contrast agent used to enhance μCT-scans (Descamps et al, 2014;Pauwels, Van Loo, Cornillie, Brabant, & Van Hoorebeke, 2013) allowing distinction between a variety of tissues including muscle, bone, ligament, and nervous tissue.…”
Section: Contrast-enhanced μCt and Segmentationmentioning
confidence: 99%
“…During this time, the specimen and solution were set to mix on an orbital shaker, kept at room temperature, and covered with foil to prevent photoreaction. PMA is a contrast agent used to enhance μCT-scans (Descamps et al, 2014;Pauwels, Van Loo, Cornillie, Brabant, & Van Hoorebeke, 2013) allowing distinction between a variety of tissues including muscle, bone, ligament, and nervous tissue.…”
Section: Contrast-enhanced μCt and Segmentationmentioning
confidence: 99%
“…In this study, the fastest stain progression was observed in I 2 E-stained specimens whereas the slowest staining progression was observed in PTA-stained specimens. This difference might occur because of the large molecular size of phosphotungstic acid (Keggin, 1934), leading to a slower movement of phosphotungstic acid than of the iodine ion (Descamps et al, 2014;Metscher, 2009b). The movement of the large-molecule contrast agent is slower than the smallmolecule agent.…”
Section: Comparison Of the 3d Brain Structure With Different Contramentioning
confidence: 99%
“…We think that the reason the CR derived from longer staining duration did not affect the visibility of 2D scan images is because the subtle differences in contrast measurable by the computer software are not detectable by our vision. Regarding visibility of scanned images, the physicochemical property of the molecules in the contrast agent is important because it affects the osmotic speed and X-ray absorption rate (Descamps et al, 2014;Gignac et al, 2016;Keggin, 1934;Metscher, 2009aMetscher, , 2009bMizutani et al, 2008 Pauwels et al, 2013). The concentration also influences the osmotic pressures, such that the contrast agent with higher concentration is absorbed more quickly by soft tissues (Visckerton, Jarvis, & Jeffery, 2013).…”
Section: Comparison Of 2d and 3d Rendering Of Brain Images Under DImentioning
confidence: 99%
“…Because most soft tissues are composed of a very similar set of molecules (largely water), they cannot readily be distinguished on an X-ray lCT scan (Richter et al 2009;Descamps et al 2014). Sometimes, PCI increases the CNR sufficiently in order to alleviate the need for soft tissue staining (Dullin et al 2017).…”
Section: Sample Preparationmentioning
confidence: 99%